Effectiveness of Combined Immunoglobulin and Glucocorticoid Treatments in a Patient With Stiff Limb Syndrome: Case Report and Review of the Literature - Huang, Juan; Meng, Huan-yu; Duan, Xian; Li, Wen-wen; Xu, Hong-Wei; Zhou, Ya-fang; Zhou, Lin (Frontiers in Neurology, 2020)
Stiff limb syndrome (SLS) is a rare autoimmune-related central nervous system disorder, resulting in stiffness and spasms of limbs since onset with rare involvement of the truncal muscles. However, SLS patients will gain notable effects by appropriate therapy focusing on symptomatic treatment and immunotherapy. We reported on a 55-year-old female who showed typical painful spasms in both lower limbs and abduction of the right eyeball partially responded to low-dose diazepam and had high-titer anti-GAD antibody. EMG only showed CMUA in the anterior tibialis and right triceps. Eventually, our patient was diagnosed with SLS and treated with intravenous immunoglobulin (IVIG) and glucocorticoid combined simultaneously. She obtained notable effects. We also review and summarize the current literature on clinical characteristics, coexisting disease, treatment and outcome of 40 patients with SLS. We hope that this report will provide a basis for further understanding of SLS and promote the formation of more advanced diagnosis and treatment processes.